Lindebjerg and Røjle Mose: Two Early Bronze Age Settlements on Fyn - Jæger, Anders; Laursen, Jesper (Journal of Danish Archaeology, 1983)
Lindebjerg and Røjle Mose - Two Early Bronze Age Settlements on Fyn.